Maternal Morbidity in Singleton versus Twin Gestations Undergoing Cesarean Delivery - Heiligenstein, Mia; Fox, Nathan (American Journal of Perinatology, 2025)
As the prevalence of twin pregnancies rises, and because of the high cesarean rate in twin pregnancies, it is imperative to estimate the maternal morbidity in twin pregnancies undergoing cesarean delivery. This study aims to clarify whether twin gestations undergoing cesarean delivery are at increased risk for maternal morbidity compared with singleton pregnancies undergoing cesarean delivery.This study was a retrospective cohort study of all singleton and twin gestations who underwent cesarean delivery in a single maternal fetal medicine and obstetrical practice from 2005 to 2023. All patients who underwent a cesarean delivery with a liveborn were included with the exception of patients with a history of a prior myomectomy, known placenta previa, or known placenta accreta spectrum. An electronic medical record was used to obtain baseline characteristics and maternal outcomes. Our primary outcome was a composite outcome for maternal morbidity. We first compared all patients undergoing primary cesarean delivery and performed subgroup analyses of patients laboring prior to cesarean delivery, scheduled primary cesarean section without labor, and repeat cesarean section. Chi-squared test, Fisher exact test, and student's t-test were utilized for statistical analysis.Of the 2,872 women meeting inclusion criteria, 2,250 had singleton pregnancies while 622 had twin pregnancies. Baseline characteristics were largely similar between groups, except for higher body mass index and incidence of preeclampsia in twin gestations. In patients undergoing primary cesarean delivery, the composite outcome for maternal morbidity did not significantly differ between singleton and twin pregnancies (0.8 vs. 1.4%; p = 0.172). However, secondary outcomes revealed higher blood loss in twin pregnancies, evidenced by both elevated estimated blood loss (EBL) and increased rate of blood transfusion (4.7 vs. 1.8%; p < 0.001). These findings remained consistent across all subgroup analyses.We observed no differences in major maternal morbidities between patients undergoing cesarean delivery for singleton or twin gestations. However, we did find significant differences in EBL and transfusion requirements for women with twin gestations.
Keywords: twin gestation; maternal morbidity; singleton gestation; cesarean delivery